THE POTENTIAL OF 3D PRINTING IN DRUG DELIVERY AND TISSUE ENGINEERING - INGLE, ANIKET S.; PATIL, KRANTI S.; PAPRIKAR, PURVA M. (International Journal of Current Pharmaceutical Research, 2025)
The pyramid of additive manufacturing, the jewel of 3-dimensional (3D) printing emerges. Over the past ten years, it has been anticipated that three-dimensional bioprinting technology will revolutionize the pharmaceutical sector. It is rapidly developing and has applications in many fields, including as the aircraft, defence, automotive, architectural, film, music, forensic, dental, audiology, prosthetics, surgery, cuisine, and fashion industries. This amazing manufacturing technique has grown in importance for pharmaceutical applications in recent years. Computer software will create a computer-aided drug (CAD) model, which will then be fed into bioprinters. The printers will identify and create the model scaffold based on material inputs. The printing process is accelerated by methods such as stereolithography, binder deposition, inkjet-based, fused deposition modelling, material extrusion, material jetting, selective laser sintering, selective laser melting, and bioprinting. Rapid prototyping, flexible design, print-on-demand, lightweight and robust components, quick and economical, and environmentally friendly are some of the unique benefits. The conceptualization of 3D printing is briefly described in this review, followed by the many techniques used. A brief explanation of the fabrication materials used in the pharmaceutical industry was given. The laser beam is directed toward the different pharmaceutical and medical uses.